Vine-shoot waste aqueous extract applied as foliar fertilizer - Sánchez-Gómez, R. (2016)
The aim of this work was to study the influence of foliar applications of different wood aqueous extracts on the amino acid content of musts and wines from Airén variety; and to study their relationship with the volatile compounds formed during alcoholic fermentation. For this purpose, the foliar treatments proposed were a vine-shoot aqueous extract applied in one and two times, and an oak extract which was only applied once. Results obtained show the potential of Airén vine-shoot waste aqueous extracts to be used as foliar fertilizer, enhancing the wine amino acid content especially when they were applied once. Similar results were observed with the aqueous oak extract. Regarding wine fermentative volatile compounds, there is a close relationship between musts and their wines amino acid content allowing us to discuss about the role of proline during the alcoholic fermentation and the generation of certain volatiles.